Eco-Friendly Novel Synthesis, Characterization of 2,3-Disubstituted 4-Thiazolidinone Derivatives and their Antimicrobial Evaluations - Pathak, Ashutosh; Malairajan, P.; Kumar Dwivedi, Parmesh; Chaturvedi, Devdutt (Asian Journal of Chemistry, 2021)
A total of nine derivatives of 4-thiazolidinone were synthesized involving the reaction of benzene-1,2-diamine with 4-aminobenzoic acid followed by reaction with substituted benzaldehyde to get the Schiff bases. These synthesized Schiff bases were further reacted with thioglycolic acid to get the desired thiazolidinones (29-37). In addition to conventional synthesis, the microwave irradiation method has also been employedfor the synthesis of these compounds which provides not only pollution free and eco-friendly environment but also excellent yields. The results showed that 2-substituted thiazolidinone derivatives exhibit good antibacterial activity. It was also recorded that the compounds containing -Cl, -NO2 group with thiazolidinone nucleus are more active than other compounds of the synthesized series.